2007
DOI: 10.1074/jbc.m609375200
|View full text |Cite
|
Sign up to set email alerts
|

p200 RhoGAP Promotes Cell Proliferation by Mediating Cross-talk between Ras and Rho Signaling Pathways

Abstract: p200 RhoGAP, a member of the Rho GTPase-activating protein (RhoGAP) family, was previously implicated in the regulation of neurite outgrowth through its RhoGAP activity. Here we show that ectopic expression of p200 RhoGAP stimulates fibroblast cell proliferation and cell cycle progression, leading to transformation. The morphology of the foci induced by p200 RhoGAP is distinct from that formed by Rac or Rho activation but similar to that induced by oncogenic Ras, raising the possibility that p200 RhoGAP may en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…In contrast, in MO + S386E and MO + R384A embryos, we observed significant increases in the intensity of RhoA-GTP at the contractile ring, the width of the RhoA activity zone, and the width of F-actin at the contractile ring ( Figure 3, A–D , and Supplemental Movie S5). To confirm that the MgcR384A phenotypes observed in vivo were due to the loss of GAP function and not to an unexpected effect caused by the loss of positive charge from the active site of the GAP domain, we tested an alternate GAP-dead mutant, R384K, which does not alter the charge of the active site (Supplemental Figure S3A; Rittinger et al ., 1997a ; Miura et al ., 2002 ; Lavelin and Geiger, 2005 ; Shang et al ., 2007 ). Similar to results with the R384A mutant, cells expressing MO + R384K also fail cytokinesis (Supplemental Figure S3, B and D) and exhibit significantly increased RhoA-GTP intensity at the furrow (Supplemental Figure S3, C and E).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in MO + S386E and MO + R384A embryos, we observed significant increases in the intensity of RhoA-GTP at the contractile ring, the width of the RhoA activity zone, and the width of F-actin at the contractile ring ( Figure 3, A–D , and Supplemental Movie S5). To confirm that the MgcR384A phenotypes observed in vivo were due to the loss of GAP function and not to an unexpected effect caused by the loss of positive charge from the active site of the GAP domain, we tested an alternate GAP-dead mutant, R384K, which does not alter the charge of the active site (Supplemental Figure S3A; Rittinger et al ., 1997a ; Miura et al ., 2002 ; Lavelin and Geiger, 2005 ; Shang et al ., 2007 ). Similar to results with the R384A mutant, cells expressing MO + R384K also fail cytokinesis (Supplemental Figure S3, B and D) and exhibit significantly increased RhoA-GTP intensity at the furrow (Supplemental Figure S3, C and E).…”
Section: Resultsmentioning
confidence: 99%
“…The repulsive guidance cue RGMa releases p120RasGAP from that interaction to mediate the inhibition of Ras activity (34). Other studies have shown that the GAP activity of p120RasGAP is inhibited when its N terminus interacts with p190RhoGAP, FAK, p200RhoGAP, or SOCS-3 (53,(61)(62)(63). Tyrosine phosphorylation of these proteins, except for p200RhoGAP, mediated the interaction (53,61,63).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the p200RhoGAP protein not only stimulates the GTPase activities of Rac1 and RhoA in vivo to regulate neurite outgrowth (Moon et al. , 2003) but also increases the Ras-GTP levels to stimulate fibroblast cell proliferation and cell cycle progression, leading to transformation (Shang et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%